2009
DOI: 10.1126/science.1173596
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Target Axon Sorting Establishes the Neural Map Topography

Abstract: Sensory information detected by the peripheral nervous system is represented as a topographic map in the brain. It has long been thought that the topography of the map is determined by graded positional cues that are expressed by the target. Here, we analyzed the pre-target axon sorting for olfactory map formation in mice. In olfactory sensory neurons, an axon guidance receptor, Neuropilin-1, and its repulsive ligand, Semaphorin-3A, are expressed in a complementary manner. We found that expression levels of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
248
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(277 citation statements)
references
References 38 publications
16
248
4
3
Order By: Relevance
“…Altered cAMP signaling, in turn, results in transcriptional dysregulation of neuronal guidance proteins and may also affect locally the behavior of the growth cones in response to external repulsive or attractive cues. These results are in line with recent findings implicating cAMP in the regulation of axonal pathfinding (29,39) as well as dendrite formation (40) and provide strong support for altered (increased) neuronal cAMP signaling due to a bona fide SCHZ risk mutation. Notably, we have recently reported an association between SCHZ and gain of function mutations in the VIPR2 locus (41) and showed that these mutations also enhance cAMP signaling in lymphocytes of patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Altered cAMP signaling, in turn, results in transcriptional dysregulation of neuronal guidance proteins and may also affect locally the behavior of the growth cones in response to external repulsive or attractive cues. These results are in line with recent findings implicating cAMP in the regulation of axonal pathfinding (29,39) as well as dendrite formation (40) and provide strong support for altered (increased) neuronal cAMP signaling due to a bona fide SCHZ risk mutation. Notably, we have recently reported an association between SCHZ and gain of function mutations in the VIPR2 locus (41) and showed that these mutations also enhance cAMP signaling in lymphocytes of patients.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, we showed that Disc1 Tm1Kara results in dysregulation of molecules involved in axon guidance and dendritic growth, whose expression is modulated by cAMP signals. Notably, the pattern of dysregulation is similar to the one reported previously in the olfactory system (29).…”
Section: Disc1 Tm1karasupporting
confidence: 85%
See 1 more Smart Citation
“…The chemotactic cues hypothesized by Cajal would fall into this category. For example, Semaphorin3A acts as a secreted repellent that prevents entry of early arriving olfactory axons into the chick olfactory bulb (Luo et al 1993;Renzi et al 2000), or in the mouse olfactory system, helps to map sensory axons from the epithelium onto specific regions of the olfactory bulb (Schwarting et al 2000;Taniguchi et al 2003;Imai et al 2009). Netrin/ unc6 is a secreted chemotactic signal produced at the ventral midlines of both vertebrates and invertebrates.…”
Section: Tropic Guidance Cuesmentioning
confidence: 99%
“…However, at the tissue level, the complex interconnectivity is masked by the distribution of neurons, such as in the stratified laminar layers of the neocortex. Although functionally related neurons generally group together (3,4), boundaries of functional units cannot be readily revealed with phenotype markers, necessitating electrophysiological studies and correlative functional outcomes. It is, therefore, necessary to differentiate physical and functional associations of neuronal populations to unravel complex networks.…”
mentioning
confidence: 99%